A Critical Review of Exercise Training in Hemodialysis Patients: Personalized Activity Prescriptions Are Needed. Issue 1 (January 2020) - Wilund, Kenneth R.; Viana, João L.; Perez, Luis M.
Abstract : Exercise training appears to have modest or inconsistent benefits in hemodialysis patients. This may be due to the low volume and intensity of exercise often prescribed. To address this, research is needed to evaluate the efficacy of individualized exercise prescriptions as a component of a comprehensive lifestyle intervention strategy that gives patients more autonomy to choose preferred types of physical activity. Abstract : This review examines the rationale for novel approaches to conducting exercise training interventions in hemodialysis patients.